The e-government of eXtensible business reporting language adoption process in Malaysia: drivers and challenges from environmental perspective - Ilias A.; Ghani E.K.; Azhar Z. (Inderscience Publishers, 2023)
This study aims to investigate drivers and challenges on XBRL adoption from mimetic, normative and coercive pressures by four regulators in Malaysia. This multiple case study involved semi-structured interviews with 16 participants. The driving factor in the knowledge and persuasion process is success stories in the form of mimetic pressure. Besides, the driving factors are motivation of regulatory pressure in the form of coercive pressure, while incentive pressure in the form of normative pressure during decision making process. In the form of normative pressure, this study shows that effective XBRL committee contributes to the XBRL adoption success. During implementation, limited trading partners and critical mass are classified as coercive pressure. Then, too reliant on external support, limited pressure from professional bodies and stakeholders, and government support are challenges to the XBRL adoption. This study shows that regulators should possess understanding about external factors and their influence on the decision to adopt XBRL. Copyright 2022 Inderscience Enterprises Ltd.